Analysis of The Influence of Leadership Competency, Staff Involvement, and Facilities on The Performance of Educational Institutions - Safngatul Ngasris Samaniyah; Ahmad Fuad Hasyim; Milna Wafirah (Program Studi Manajemen Pendidikan, 2024)
This study aims to analyze the influence of leadership competence, staff involvement, and facility quality on the perception of effectiveness in educational organizations. A quantitative approach is used with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to test the relationship between leadership competence, staff engagement, facilities, and perception of organizational effectiveness. Data was obtained from a survey of employees of educational institutions with a total of 100 respondents selected using purposive sampling. The results of the analysis show that staff facilities and involvement have a significant effect on the perception of the effectiveness of educational organizations, while leadership competencies have a lower direct influence. These findings indicate that adequate facilities and staff involvement are important factors in shaping a positive perception of organizational effectiveness. This study contributes to the literature on internal factors that affect the effectiveness of educational organizations, in particular by exploring the influence of a combination of variables of leadership competence, facilities, and staff engagement. This study closes the knowledge gap related to the comprehensive impact of these factors on the perception of organizational effectiveness. These findings provide recommendations for educational leaders to improve resource allocation to support facilities and increase staff involvement in decision-making. This is important for creating a conducive work environment, which will contribute to the perception of the organization's effectiveness and the potential for overall productivity improvement